Comparative study of autonomic function in diabetics and yoga practitioners using Ewing’s battery - Tasneem Amadawala; Charushila Rukadikar; Dileep Deshpande (Journal of Family Medicine and Primary Care)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by high blood sugar levels. It significantly increases the risk of cardiovascular diseases and autonomic neuropathy. Yoga has been shown to improve autonomic function and glycemic control in diabetic patients. Objective: To compare the autonomic nervous system (ANS) function between diabetic patients and regular yoga practitioners using Ewing’s battery tests. Methods: This cross-sectional study included 270 participants, divided into two groups: 135 diabetics (Group I) and 135 yoga practitioners (Group II). Participants’ height, weight, and BMI were measured. ANS function was assessed using Ewing’s battery tests, which included heart rate (HR) and blood pressure (BP) responses to various stimuli. Statistical analysis was performed using SPSS, with significance set at P ≤ 0.05. Results: Diabetic participants showed lower HR responses to standing from a supine posture, the Valsalva maneuver, and slow deep breathing, indicating impaired parasympathetic function. They also exhibited higher BP responses to the cold pressor test, sustained handgrip, and standing, reflecting sympathetic overactivity. In contrast, yoga practitioners demonstrated better autonomic function with higher HR responses and lower BP responses in these tests. The findings suggest that yoga promotes parasympathetic dominance and reduces sympathetic overactivity. Conclusion: Regular yoga practice significantly improves autonomic function in individuals, including those with diabetes. These results support the incorporation of yoga as a complementary therapy in diabetes management to enhance cardiovascular health and reduce autonomic dysfunction.